Presentation of Carcinoma Breast in Pakistan - A Study of 60 Cases - AHMAD, A; NAZ, F; KHAWAJA, M A; HAQ, A U; MALIK, S N; KHAN, S A (Annals of King Edward Medical University, 2018)
A study of 60 cases presenting with cancer of the breast in the surgical Unit-II of Mayo Hospital, Lahore. It was found that established risk factors for the development of carcinoma breast like nulliparity, infertility, old age early menarche, late menopause and positive family history bear a different relationship to the occurrence of cancer breast in Pakistani women. Cancer occurred predominantly in the younger age group (less than 50 years) with high parity (average 4-5 children) and at least 6 years of lactation in the lifetime of each woman. Why this change in presentation of cancer breast? Has it been there since the beginning or a recent change? The answer is yet to be found.